What are the challenges of multilevel governance for urban sustainability? Evidence from Ottawa and Canada's national capital region. (June 2016) - Zeemering, Eric S.
Abstract: Urban sustainability is a priority for cities, challenging public administrators to coordinate action on environmental policy, economic development and social policy. Multilevel governance is now a popular theoretical framework but research must illuminate the constraints on local administrators. This case study reviews efforts of public administrators in the City of Ottawa and Canada's national capital region to implement sustainability policies with collaborative governance, but new governance relationships are constrained by traditional intergovernmental relations. Case study research illuminates the challenges of multilevel governance for local governments and provides insights on the pursuit of sustainability with environmental programs, land use, and urban and development by Crown corporations.